Pengaruh literasi keuangan terhadap perilaku keuangan mahasiswa - Paramitha, Sindy (Maliki Interdisciplinary Journal, 2026)
Financial literacy is an important skill that students need to deal with the complexities of managing money in the modern era. Students often face various financial decisions, such as managing their pocket money, using digital financial products, and making spending choices that can affect their long-term financial situation. The problem is that many students have low financial literacy, which can lead to unhealthy financial behaviors. This study aims to analyze how financial literacy affects students’ financial behavior. The approach used is a literature review, looking at previous research and academic works, including those from lecturers at UIN Maulana Malik Ibrahim Malang, obtained through the institution’s repository. The findings show that financial literacy has a significant impact on students’ financial behavior, such as budgeting skills, saving habits, and making rational financial decisions. Students with higher financial literacy tend to have more responsible financial behavior compared to those with lower literacy. Therefore, improving financial literacy through formal and informal education is a strategic solution in shaping healthy and sustainable financial behavior among students.